Evolution of fitness trends through a comparative lens - Golubeva G.N.; Dvorkina N.I.; Starkova E.V.; Peshkova N.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to examine the evolution of fitness trends in Russia and globally over a two-year period. Methods and structure of the study. Based on the insights of experts, a questionnaire was created using Google Forms. The questionnaire included 50 fitness trends, with one question for each trend. Respondents were asked to select and rank the top 20 trends. The questionnaire was distributed to 963 individuals from Russia aged 18 and above. A total of 350 individuals completed the questionnaire. The survey also collected information about the respondents’ city of residence and their occupation. Results and conclusions. Twenty fitness trends of 2024 have been identified, of which 50% are new: functional training; outdoor training; group training; online training; personal training; yoga; wearable technology; dance training; pilates; fitness in parks; healthy lifestyle at work; fitness travel; regular walking; circuit training; training with massage roll; home gyms; fitness marathons; fitness on the go/ passing workout; cycling, roller skating; crossfit.